Life-world Knowledge and Scientific Knowledge: An Epistemological Rupture - Métioui, Abdeljalil; Trudel, Louis (Advances in Social Sciences Research Journal, 2018)
The purpose of this paper is to highlight the epistemological rupture between the "life-world knowledge" and the "scientific knowledge." Their confrontations are essential in the teaching context.